INTERCHAIN SILICONE INTERACTIONS: STRUCTURING SILICONE ELASTOMERS USING PHYSICAL, COVALENT, AND INTERFACIAL CHEMISTRY - Fawcett, Amanda S. (My University, 2013)
Silicone polymers, particularly PDMS (poly(dimethylsiloxane)) exhibit a wide range of exceptional properties including optical transparency, biostability, hydrophobicity and excellent oxygen transmissibility that make them extremely useful in a wide range of applications, particularly as biomaterials. Current methods for the preparation of silicone elastomers have been well documented, however, silicone elastomers are thermoset materials and once cured, they cannot be reformed without chemical intervention. The properties of silicones that make them a popular material choice in a wide variety of industries also make them un-responsive and non-reusable often limiting their application to one primary purpose.
This thesis aims to further understand the mechanisms of silicone polymer chain interactions and how the chemistry of polymer modification can alter the mechanical and chemical properties of materials. The effects of distinctive functional groups (coumarin) on silicone chains to allow for both the formation of thermoplastic silicone elastomers and stimuli-responsive elastomers for reversible crosslinking are explored.
A companion study examined a different way to form silicone elastomers. The Piers- Rubinsztajn reaction was used to create elastomers and foams rapidly and under relatively mild conditions using very small quantities of the catalyst B(C6F5)3. The factors required to create – on demand – a foam or an elastomer, and the strategies to control physical properties, including bubble density and modulus, are explored.
Silicone foams that were structured in a completely different way are described. Allyl- modified PEG (poly(ethylene glycol)) was found to structure foam mixtures precure. The product foam after cure was amphiphilic, due to the presence of both silicone and PEG constituents. The origins of bubble stabilization and the ability to control foam properties are described.
Keywords: Silicone; Polymer; Thermoplastic Elastomer; Elastomer; Foam; Photoresponsive Silicone; Materials Chemistry; Polymer Chemistry; Materials Chemistry